Diagnostic accuracy of SARS-CoV-2 antigen test in the pediatric population: A systematic review and meta-analysis - Cheng-Chieh Chen; Shih-Yen Chen; Shiuh-Bin Fang; Shou-Cheng Lu; Chyi-Huey Bai; Yuan-Hung Wang (Pediatrics and Neonatology, 2023)
Background: Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has caused the global coronavirus disease 2019 (COVID-19) pandemic. Rapid identification and isolation of patients infected with SARS-CoV-2 are critical methods for blocking COVID-19 transmission. The advantages of antigen tests, such as their relatively low cost and short turnaround time, can contribute to the prompt identification of infectious individuals. However, the diagnostic accuracy of antigen tests for COVID-19 in children remains inconclusive. This meta-analysis aimed to evaluate the diagnostic performance of antigen tests for SARS-CoV-2 in the pediatric population. Methods: We conducted a literature search for relevant studies in the PubMed, Embase, Google Scholar, and Biomed Central databases. Studies evaluating the diagnostic accuracy of antigen tests for SARS-CoV-2 in pediatric patients were included. In addition, we included studies that provided sufficient data to construct a 2 × 2 table on a per-patient basis. The final literature search was performed on October 10, 2021. Days after symptom onset, asymptomatic and symptomatic individuals may have been potential sources of heterogeneity. The overall sensitivity and specificity of the antigen tests were generated using a bivariate random-effects model. Results: Five studies with 4400 participants were included. The meta-analysis of antigen tests generated a pooled sensitivity of 65.9% (95% CI: 52.8%–77.0%) and pooled specificity of 99.9% (95% CI: 98.9%–100.0%). A subgroup analysis of studies reporting antigen test data for symptomatic patients showed a pooled sensitivity of 64.5% and a pooled specificity of 99.7%. The subgroup analysis of studies that included 881 asymptomatic participants generated a pooled sensitivity of 48.4% and a pooled specificity of 99.5%. Conclusion: Antigen tests exhibit moderate sensitivity and high specificity for detecting SARS-CoV-2 in children. Antigen tests might have moderate sensitivity for detecting SARS-CoV-2 in symptomatic children, and serial testing might effectively prevent further SARS-CoV-2 transmission.